Human-elephant conflict characteristics in Ulu Tembeling region / Mohd Ruzed Embong - Embong, Mohd Ruzed (2015)
Human-Elephant Conflicts (HEC) becomes a major concern among natural resources managers. The numbers of HEC reported each year contribute to thousands of ringgit of loses to local farmers who depend on agriculture as their main income. Being an agriculture region in Pahang, Ulu Tembeling is facing HEC thus pressuring local community to sustain their income. Being geographically marginalized, the problems arise and worsen when HEC cases were not attended accordingly and the intensity of the conflict has never been measured. This thesis is conducted in order to identify the extent of the HEC throughout the Ulu Tembeling region. Spatial distributions of the conflicts are charted in order to establish the exact spatial distribution and thus help resources managers toward planning and managing the natural resources. Data were collected through Snow Ball Sampling technique and supported by ground trotting for verification. Spatial data were located and plotted onto topographical map and questionnaire survey forms were designed based on Data Collection and Analysis Protocol for HEC by International Union for Conservation of Nature (IUCN)-African Elephant Specialist Group. Descriptive analyses were employed to quantify the extent of the HEC therefore providing crucial information for Ulu Tembeling HEC. The study found that the intensity of the conflict amounted to RM 54,040.00 of loss during a one year study period; representing 26.25 % of trees damage which affected incomes of individuals who are barely above poverty line. Spatial distributions of the conflict found most to be concentrated at Kampung Sat and Kampung Mat Daling and perhaps crop raiding elephant entry point were from nearest forest reserve complex which are located next to victims rubber plantation. HEC was found to be intense among a female and calf herd which is correlated with intermediate rubber plant stage, perhaps due to crop palatability compared to other stages while most intense HEC was during the night with duration less than three days, most of HEC has been found to occur during the dry season. Elephants, resources and victims involved in the conflict pose particular characteristics which provide a clearer understanding toward HEC in Ulu Tembeling region. Existence of reliable HEC record and data are useful for wildlife and resource managers dealing with increasing human-wildlife conflicts. It is recommended that DIu Tembeling region to have a standardized data record on HEC so the issues can be resolved appropriately.